Debt Securities Issuance in Malaysia: Type of Security and Impact on Equity Returns, Systematic and Total Risk - Chin, Sze Kim (2010)
The study examines the association of company characteristics with debt securities offers and explores whether there is any significant difference between hybrid and non-hybrid debt securities issuers. In addition, the study investigates the impact of debt securities issuance on the equity market behaviour of the issuers. The regression result found a positive and significant association for company size but negative association for managerial ownership structure with debt securities issuance. Subsequently, using logistic regression techniques, the study revealed that companies with higher profitability and higher managerial ownership appear to favour non-hybrid debt securities to hybrid debt securities. Nonetheless, the study found no significant difference between hybrid and non-hybrid debt securities issuers in terms of company size, asset tangibility and growth opportunities. The event study results reveal that overall debt securities issuers experience increase in company return following the debt securities issuance and decrease in systematic risk while total risk remain unchanged. Hybrid debt securities experience significant fall in stock returns and systematic risk but an increase in total risk. Non-hybrid debt securities issues, however, are found to have no impact on equity market behaviour. Findings of the study imply the need to promote participation from financially strong companies in the hybrid debt securities segment. Further, the decline in systematic risk for debt securities issuing companies could motivate the issuance of debt securities and thus improve the market liquidity. Finally, non-hybrid debt securities are not appropriate to be used for market signal as no impact on market behaviour was found following the non-hybrid debt securities issuance.